2002
DOI: 10.1023/a:1021440220329
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Using gas chromatography with flame ionization detection (FID) and electroantennographic detection (EAD) in parallel, butanoic acid, skatole, and (E)-2,6-dimethyl-6-octen-2-ol were identified as constituents of the abdominal sexattracting secretion of the male dung beetle, Kheper subaeneus, which reproducibly elicited EAD responses in male and female antennae. This is the first report of the occurrence of (E)-2,6-dimethyl-6-octen-2-ol as a natural product, for which the name (E)-subaeneol is proposed. In so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…After evaporating the solvent in vacuo, the resulting oil was chromatographed in a silica gel column (R)-2,6-Dimethyl-5-hepten-1-ol (2-R). Aldehyde 1-R (prepared as reported 3) ) was reduced as already described, using LiAlH 4 to give alcohol 2-R. ½ D 24 þ9:1 (c 1.0 CHCl 3 ). (R)-2,6-Dimethyl-5-heptenyl acetate (3-R).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After evaporating the solvent in vacuo, the resulting oil was chromatographed in a silica gel column (R)-2,6-Dimethyl-5-hepten-1-ol (2-R). Aldehyde 1-R (prepared as reported 3) ) was reduced as already described, using LiAlH 4 to give alcohol 2-R. ½ D 24 þ9:1 (c 1.0 CHCl 3 ). (R)-2,6-Dimethyl-5-heptenyl acetate (3-R).…”
Section: Methodsmentioning
confidence: 99%
“…In order to determine the stereochemistry, (R)-2,6-dimethyl-5-hepten-1-ol (2-R) was synthesized by way of (R)-2,6-dimethyl-5-heptenal (1-R) which had been prepared according to the synthetic route reported, 3) starting from commercially available (R)-3,7-dimethyl-1,6-octa-diene (4) with subsequent epoxidation and ozonolysis ( Fig. 3).…”
mentioning
confidence: 99%
“…Favila [ 7 ] demonstrated that fresh male secretions, probably from the fifth abdominal sternite, were attractive to conspecific females, and secretions from different glands in Canthon species serve to deter competitors and predators [ 5 , 8 ], leading Cortez et al [ 9 ] to suggest that these secretions may serve multiple purposes. This idea is supported by studies on other dung beetles: for example, male secretions from glands situated on the first abdominal sternite of Kheper species are involved in mating [ 10 , 11 ], while adults of Oniticellus egregius (Klug, 1855) produce secretions from the lateral edges the anterior abdominal segments that play a role in defence [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 93%
“…These constituents and constituent 4 reproducibly gave EAD responses in male as well as female antennae. 3-Methylindole elicited EAD responses in the antennae of the other three Kheper species investigated thus far [8], [19] and [20].…”
Section: Structural Elucidationmentioning
confidence: 99%
“…Subaeneol, although giving a strong EAD response, was present in an extract of the abdominal secretion in such a low concentration that it gave a barely detectable FID signal. The major volatile constituent of the secretion of K. subaeneus males, (S)-(+)-3,6-dimethyl-5-heptenoic acid, elicited EAD responses in male antennae in only a few instances [8].…”
Section: Introductionmentioning
confidence: 99%